The EU's role in global governance the legal dimension - Van Vooren, Bart.; Blockmans, Steven; Wouters, Jan, 1964- (Oxford : Oxford University Press, 2013)
The rise to power of such countries as China and Brazil, as well as the EU sovereign debt crisis, have deeply affected the capacity of the EU to influence global realities. This book brings together prominent legal scholars and practitioners to investigate the extent to which the EU can shape this on-going re-orientation of the international scene.
Description based on print version record.
Includes bibliographical references and index.
Keywords: International organization; European Union